Book Museums of the Kingdom of Belgium as a Space of Socio-Cultural Communication - Олена Григоревська (Культура і мистецтво у сучасному світі)
The aim of the article is to analyse the features of the development of socio-cultural space of two well-known book museums in the Kingdom of Belgium: the Royal Library of Belgium and the Wittockiana Museum; to focus on the methods of promoting the collections that form the basis of the museum holdings, information services, and educational programmes. Results. The Royal Library of Belgium is defined as a unique high-tech socio-cultural space where the cultural life of medieval Europe is explored through images, histories, and characters from the Library of the Dukes of Burgundy. The analysis of the museum’s website and blog materials leads to the conclusion that the national library takes its communication with user audiences very seriously. The Wittockiana is a museum of book art and bookbinding and an organiser of projects. The museum engages in diverse exhibitions, research, and educational activities. An interesting component of the museum’s socio-cultural space is the bookbinding workshop, which serves as a basis for educational projects. The scientific novelty of the study is that for the first time in the Ukrainian scientific discourse, the development of the socio-cultural space of contemporary European museums is considered using the example of the book museums of the Kingdom of Belgium. Conclusions. The successful formation and development of the socio-cultural space of contemporary European book museums is largely the result of persistent and multifaceted research activities of such institutions. The Royal Library of Belgium is a vivid example of the development of the “media” concept of a museum as a socio-cultural institution. The museum’s socio-communication space is developing in many areas, including the expert environment and public relations. The educational services of the Wittockiana Museum and the partner book workshop of the Royal Museum of Mariemont are considered as an experience worthy of in-depth study and implementation in Ukraine.